Respuesta :
[tex]\bf \begin{array}{cccccllllll}
{{ a}}^2& + &2{{ a}}{{ b}}&+&{{ b}}^2\\
\downarrow && &&\downarrow \\
{{ a}}&& &&{{ b}}\\
&\to &({{ a}} + {{ b}})^2&\leftarrow
\end{array}\qquad
\qquad \qquad
\begin{array}{cccccllllll}
{{ a}}^2& - &2{{ a}}{{ b}}&+&{{ b}}^2\\
\downarrow && &&\downarrow \\
{{ a}}&& &&{{ b}}\\
&\to &({{ a}} - {{ b}})^2&\leftarrow
\end{array}\\\\
-------------------------------[/tex]
[tex]\bf \begin{array}{llll} p^2+14p+49\\\\ p^2+2(p)(7)+7^2 \end{array} \qquad \implies\qquad \begin{array}{cccccllllll} {{ p}}^2& + &2{{ (p)}}{{ (7)}}&+&{{ 7}}^2\\ \downarrow && &&\downarrow \\ {{ p}}&& &&{{ 7}}\\ &\to &({{ p}} + {{ 7}})^2&\leftarrow \end{array}[/tex]
[tex]\bf \begin{array}{llll} p^2+14p+49\\\\ p^2+2(p)(7)+7^2 \end{array} \qquad \implies\qquad \begin{array}{cccccllllll} {{ p}}^2& + &2{{ (p)}}{{ (7)}}&+&{{ 7}}^2\\ \downarrow && &&\downarrow \\ {{ p}}&& &&{{ 7}}\\ &\to &({{ p}} + {{ 7}})^2&\leftarrow \end{array}[/tex]